Identifikasi Service Blueprint di Desa Wisata Kebontunggul (Lembah Mbencirang), Kecamatan Gondang, Kabupaten Mojokerto - Agung Yoga Asmoro; M. Nilzam Aly; Handika Fikri Pratama (Politeknik Negeri Bengkalis, 2020)
This study aims to comprehend the actual conditions of business processes and to identify service blueprints in the Kebon Tunggul Tourism Village